INTELLECTUAL CAPITAL DISCLOSURE: STUDI KOMPARASI ANTARA UNIVERSITAS DI INDONESIA DAN MALAYSIA - Ihyaul Ulum; Andi Tenrisumpala; Endang Dwi Wahyuni (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
The aim of this study is to identify the intellectual capital disclosure practices of Indonesia and Malaysian universities. 5 best universities from Indonesia and Malaysia based on webometrics 2015 survey was used as the object of study. Intellectual capital component used in this study is a framework developed by Ulum (2011) which consist of 46 items: 8 items human capital, 23 items structural capital, and 15 items relational capital. Mann-Whitney test with SPSS 21 was used to analyze the data. The results showed that there were no differences between universities in Indonesia and Malaysia in disclosing information about the IC through their website. Based on the amount of information disclosed, both universities in Indonesia and Malaysia were more likely to disclose information in a narrative format.DOI: 10.15408/akt.v9i1.3582